On Identifying the Factors that Affect Turnover Intention - Wibawa Prasetya; Ma'ruf Akbar; Billy Tunas (Journal of Business and Behavioural Entrepreneurship, 2018)
The present paper attempted to determine the factors that might affect turnover intention. Although the research participants consisted of 234 employees of PT Petrosea, only samples from 152 employees were used. The samples were derived by using the simple random sampling method and collected through a questionnaire. The collected data was then analyzed based on the Structural Equation Modeling (SEM) with an application software called Lisrell. The results showed that the following variables, adversity quotient, job satisfaction, and job motivation, did not have a significant effect on turnover intention. However, the regression equation showed that the higher scores of adversity quotient, job satisfaction, and job motivation would make turnover intention lower. Thus, to prevent staff or labor turnover, a company is advised to select those prospective employees that have a higher score of adversity quotient since it has a significant effect on job satisfaction and motivation. This might result in decreasing turnover intention.